What happens to air when it is heated

Answers

Answer 1
Answer:

Answer:

It expands

Step-by-step explanation:

The energy put into it causes it to move faster and expand


Related Questions

Last Friday Adam had $22.33. Over the weekend he received some money for cleaning the attic he now has $32 how much money did he receive
How do you round 78.539 to the nearest hundredths
Use long division to convert โˆ’1464to a decimal.
Find the value of x. Then find the measure of Arc AN. Show work on a piece of paper.a) Value of x = b) Arc AN =
Which rotation about its center will carry a regular decagon onto itself?A. 54 B. 162C. 198D. 252Please explain!!!

The sum of two numbers is 264. One number ends with a zero. If this zero is erased, you get the second number. Find these numbers.

Answers

Answer:

240; 24

Step-by-step explanation:

Given that:

Sum of two numbers = 264

One number ends with '0'

Second number = first number without '0'

Let the first number be 'a'

Since the second number is the first number with '0' erased, then,

Second number = (a รท 10)

Therefore, the expression becomes :

a + a/10 = 264

Multiply the equation by 10

10a + a = 2640

11a = 2640

a = 2640/11

a = 240

Therefore ;

a = 240 ;

a/10 = 240/10 = 24

The numbers are 240 and 24

Which of the following sets of values is a soulution to the following system of liner expressions, 4x+y=24 x-y=-4x=4, y=8
x=2, y=6
x=1, y=1
x=5,y=4

Please show your work :)
will mark brainliest

Answers

Hope this helps. I think it's right? haha haven't done this in a while.

PLEASE HELP!!!
6x - 2y = 10 for y when x = 2

Answers

6(2)-2y=10
12-2y=10
-12      -12
-2y=-2
divide by -2
y=1
the answer is y equals 1 

Rearrange x=3g+2 to make g the subject.

Answers

We have: x = 3g + 2

Subtract 2 from the both sides, 
x - 2 = 3g + 2 - 2
x - 2 = 3g

Now, Divide 3 from both sides, 
(x-2)/3 = 3g/3
g = x-2 / 3

In short, Your Answer would be x-2 /3

Hope this helps!

The concept of the linear system, subtraction, and division is applied.

g is taken as a subject then the equation is \rm g = (x - 2)/(3).

What is the linear system?

It is a system of an equation in which the highest power of the variable is always 1. A one-dimension figure that has no width. It is a combination of infinite points side by side.

Given

x = 3g + 2 is a single linear variable equation.

Rearrange x = 3g + 2 to make g the subject.

Subtract 2 from the equation.Then

x - 2 = 3g

Divide the equation by 3. Then

\rm g = (x - 2)/(3)

Thus, g is taken as a subject then the equation is \rm g = (x - 2)/(3).

More about the linear system link is given below.

brainly.com/question/20379472

A telephone company charges a fixed monthly rate plus a rate per megabyte of data used. The company charges $155 for 100 megabytes and $245 for 200 megabytes. An equation can be written to show the relationship between the total megabytes of data used (x) and the total monthly charges (y). Which of the following best describes the steps to draw the graph? Draw a graph that joins the points (155, 100) and (245, 200) and has a slope = 0.9 Draw a graph that joins the points (155, 100) and (245, 200) and has a slope = 1.1 Draw a graph that joins the points (100, 155) and (200, 245) and has a slope = 1.1 Draw a graph which joins the points (100, 155) and (200, 245) and has a slope = 0.9

Answers

Answer:

Draw a graph that joins the points (100, 155) and (200, 245) and has a slope = 0.9

Step-by-step explanation:

x variable represents total megabytes of data used

y variable represents total monthly charges

The company charges $155 (y) for 100 megabytes (x) means that the point (100, 155) belongs to the equation.

The company charges $245 (y) for 200 megabytes (x) means that the point (200, 245) belongs to the equation.

With these two points, the slope is computed as follows:

(245 - 155)/(200 - 100) = 0.9

Find the discriminant for this equation. x2 + 3x + 1 = 0

Answers

Answer:

5

Step-by-step explanation:

if ax^2 +bx + c ====>discriminant formula is b^2 - 4ac  from the quadratic formula

x2 + 3x + 1 = 0

Then;

a=1

b=3

c=1

b^2 - 4ac = 3^2 -4*1*1

= 9-4

= 5

โ€‹

โ€‹